Mengoptimalkan Promosi yang Efektif untuk Penerimaan Siswa Baru Sekolah Kuncup Melati di Semarang - Masine Slahanti; Rini Indah Sulistyowati; Sofyandanu Setiadi (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
Kuncup Melati School consists of Kindergarten, Elementary School and Junior High School is one of the private schools located in the middle of the city which is quite strategic and very easy to access and in a densely populated area. In addition to being in a strategic and densely populated location, this school is a private school that does not charge any fees to its students. Funded by a Khong Kauw Hwee Foundation.Every year like other private schools, it opens registration opportunities, but even though the school is free, there are not many students, especially the community in the school environment, the school already has social media which is a means of information and promotion of activities and activities from the school, but registrants who enter this school sometimes do not meet the quota provided by the school. On this occasion, the Community Service Team will carry out activities with the theme of optimizing effective promotional media that can help achieve the target of students who register at Kuncup Melati School. , namely with promotional activities other than social media can be done with other media. The hope is that with this promotional optimization activity, it can increase public interest in entering school at Kuncup Melati.